Multi Intelligent Fuzzy Integration (Mifi) Support Vector Machines for the Mammogram Classification - Jayandhi, G; R.Dhaya, Dr; R.Kanthavel, Dr (International Journal of Engineering and Technology, 2018)
Breast cancer is the most important problem across the globe in which the 80% of the women are suffering without knowing the causes and effects of the cancer cells. Mammogram Image is the most powerful tool for the diagnosis of the Breast cancer. The analysis of this mammogram images proves to be more vital in terms of diagnosis but the accuracy level still needs improvisation. Several intelligentÂ Â techniques are suggestedÂ Â for the detection of Micro calcification in mammogram images. The new technique MIFI-SVM has been proposed which integrates the GLCM features along with the Fuzzy Support Vector Machines. ROI Segmentation using Saliency maps has been used for the proposed algorithm andÂ feature is extracted using GLCM and fed to Fuzzy Support Vector MachinesÂ Â TheÂ MIAS datasets has been used for testing the proposed algorithm and accuracy, sensitivity has been measured which proves to be better whenÂ compared to otherÂ Multi-level SVMâ€™s, C-SVM and Neural Networks.Â Â